Flexible transparent polyimide film and preparation method thereof

Through the combination of diamine, dianhydride and additives with specific ratios, the polymerization reaction and high-temperature treatment are optimized, and the problem of insufficient flexibility of traditional polyimide films is solved, and the polyamide with high optical transparency and heat resistance is achieved Imine film, suitable for flexible display field.

CN119306945AActive Publication Date: 2025-01-14RAYITEK HI TECH FILM CO LTD +1

Patent Information

Application Number
CN202411517713.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-14
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

While improving optical transparency and heat resistance, traditional transparent polyimide films have insufficient flexibility, complex processes and high costs, which limits their industrial promotion.

Method used

Through the specific diamine and dianhydride composition ratio, combined with antioxidants, ultraviolet absorbers and hydrophobic vapor-phase silica and other additives, the polymerization reaction and high-temperature imidation process are optimized to prepare high optical transparency and resistance Flexible transparent polyimide film with thermal and mechanical properties.

Benefits of technology

It significantly improves the optical and mechanical properties of the polyimide film, reduces the yellowing index, and meets the technical needs in the field of flexible display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107172410000061
    Figure BDA0005107172410000061
  • Figure BDA0005107172410000071
    Figure BDA0005107172410000071
  • Figure BDA0005107172410000081
    Figure BDA0005107172410000081
Patent Text Reader

Abstract

The invention provides a flexible transparent polyimide film and a preparation method thereof, and relates to the technical field of high polymer materials. The polyimide film is prepared from diamine and dianhydride through a polymerization reaction. The diamine comprises a first diamine and a second diamine; the first diamine is aromatic diamine containing a rigid group; the second diamine is diamine containing imidazole; the dianhydride comprises first dianhydride and second dianhydride; the first dianhydride is selected from at least one of 3, 3, 4, 4-diphenyl sulfone tetracarboxylic dianhydride, 4, 4 '-biphenyl tetracarboxylic dianhydride and benzophenone tetracarboxylic dianhydride; and the second dianhydride is selected from 2, 2 '-(1, 4-piperazine diacyl)-succinic anhydride or 2R, 5R, 7S, 10S-naphthalene tetracarboxylic dianhydride. According to the polyimide film prepared by the method, the optical performance is remarkably improved, and meanwhile, better heat resistance and mechanical performance are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a flexible and transparent polyimide film and a preparation method thereof. Background Art

[0002] Polyimide (PI) refers to a type of polymer containing an imide ring on the main chain. It has excellent mechanical properties, high and low temperature resistance, and radiation resistance, and has high resistivity and low dielectric constant. PI has an extremely wide temperature application range and does not crack in liquid helium at -269°C. The thermal decomposition temperature generally exceeds 500°C, and some systems can reach above 600°C. It is one of the special engineering plastics with the highest thermal stability to date. In addition, PI also has the advantages of excellent mechanical properties, resistance to organic solvents, radiation resistance, aging resistance, flame retardancy and self-extinguishing. According to the product form, PI materials can be divided into a variety of product forms such as films, fibers, thermosetting resins, photosensitive adhesives, slurries, separation membranes or diaphragms, aerogels, foams, etc., and have important applications in the fields of electronics and microelectronics, aerospace, mechanical and electrical engineering, etc.

[0003] In recent years, with the development of high-tech industries, the flexibility and transparency of optoelectronic devices have become an inevitable development trend. Colorless and transparent polyimide has the characteristics of transparency, light weight, impact resistance, and excellent heat resistance. It has received more and more attention in the fields of patterned display devices, liquid crystal orientation layers, optical films, organic photovoltaic solar panels, flexible printed circuit boards, and touch panels. In order to achieve true transparency and flexibility of organic optoelectronic devices represented by OLED, in addition to transparency and heat resistance, the excellent comprehensive mechanical properties of polyimide films are also important influencing factors for the application of flexible optoelectronic material layers.

[0004] Traditional polyimide films are brown or yellow. In order to minimize the charge transfer interactions between or within molecules to produce colorless and transparent polyimide, researchers generally introduce special groups into the main chain structure of the molecule, such as large substituent side groups that can impart a larger free volume, or asymmetric structures. However, in most cases, the introduction of these functional groups will sacrifice the flexibility of the film. Therefore, conventional transparent polyimide materials have good optical properties, but their process is complicated, the product flexibility is insufficient, and the yield is low.

[0005] Chinese patent application 201810688078.5 discloses a fully aromatic colorless transparent polyimide film and its preparation method, using a diamine monomer 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene with a trifluoromethyl side group and an intermediate ether bond as a raw material, and polymerizing it with 2,3,3',4'-diphenylether tetracarboxylic dianhydride containing an ether bond and isomers in the middle, and then synthesizing a thermoplastic polyimide material by a chemical imidization method, and a polyimide film can be prepared by dissolving, coating and volatilizing solvents. The fully aromatic colorless transparent polyimide film prepared by this invention has high optical transparency and thermal stability, but the fully aromatic CPI generally mainly introduces fluorine atoms or fluorine-containing groups to hinder the formation of intermolecular charge transfer complexes, but the fully aromatic CPI has high cost, complex processing technology, and poor surface adhesion of transparent films, which limits the industrial promotion of the fully aromatic CPI.

[0006] Chinese patent application 201810841797.6 provides a low birefringence, high Tg transparent polyimide film and its preparation method. The polyimide film is a polyimide polymer containing a nonlinear structure formed by polycondensation of a mixture of dianhydride and diamine, wherein the dianhydride used includes an asymmetric dianhydride with a molar ratio of 20% to 80%, and other dianhydrides with a molar ratio of 80% to 20%; the diamine used includes an meta-substituted diamine with a molar ratio of not more than 50% and other diamines with a molar ratio of not less than 50%. The transparent polyimide film has a transmittance of greater than 85% at 550nm, a birefringence of less than 0.005, and a Tg of greater than 300°C, but its yellowness index is generally between 5-6.

[0007] Based on this, a new polyimide film and its preparation method are developed, so that the prepared polyimide film has high optical transparency, excellent heat resistance, optical properties and comprehensive mechanical properties. The development of this type of material can meet the increasingly urgent technical needs in the fields of advanced electronics and flexible displays. It is the research focus of researchers in this field and is of great significance. Summary of the invention

[0008] In view of the above problems, the present invention provides a flexible and transparent polyimide film and a method for preparing the same. By using specific components and proportions and optimizing the preparation method, the optical properties of the polyimide film are significantly improved while obtaining better heat resistance and mechanical strength.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] In one aspect, the present invention provides a flexible and transparent polyimide film, which is prepared by polymerization of diamine and dianhydride;

[0011] The diamine comprises a first diamine and a second diamine;

[0012] The first diamine is an aromatic diamine containing a rigid group;

[0013] The second diamine is a diamine containing imidazole;

[0014] The dianhydride comprises a first dianhydride and a second dianhydride;

[0015] The first dianhydride is selected from at least one of 3,3,4,4-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-biphenyltetracarboxylic dianhydride (BPDA) and benzophenonetetracarboxylic dianhydride (BTDA);

[0016] The second dianhydride is selected from 2,2'-(1,4-piperazine dicarboxylic acid)-disuccinic anhydride (PDA) or 2R,5R,7S,10S-naphthalenetetracarboxylic dianhydride (HNTDA).

[0017] Preferably, the first diamine is selected from at least one of 9,9-bis[4-(4-aminophenoxy)phenyl]xanthene (BAPX), 2-(3,5-diaminophenyl)-9,9'-spirobifluorene (35DABSBF), 2-(2,4-diaminophenyl)-9,9'-spirobifluorene (24DABSBF) and 2-bis(4-aminophenyl)hexafluoropropane (BIS-A-AF);

[0018] Preferably, the second diamine is selected from at least one of 2-(4-aminophenyl)-5-aminobenzimidazole (4APBI), 2-(3-aminophenyl)-5-aminobenzimidazole (3APBI), diaminodiphenyl ether (ODA) and 2,2'-dimethyl-4,4'-diaminobiphenyl (DMBZ);

[0019] Preferably, the molar ratio of the total amount of diamine to the total amount of dianhydride is 1-1.2:1-1.2; more preferably, the molar ratio of the total amount of diamine to the total amount of dianhydride is 1:1.05.

[0020] Preferably, the molar ratio of the first diamine to the second diamine is 3-7:2-6; further preferably, the molar ratio of the first diamine to the second diamine is 4-6:3-4;

[0021] Preferably, the molar ratio of the first dianhydride to the second dianhydride is 6-9:1-4; more preferably, the molar ratio of the first dianhydride to the second dianhydride is 7-8:3-4.

[0022] Preferably, the polymerization reaction is carried out in the presence of a solvent;

[0023] Preferably, the solvent is selected from at least one of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), r-butyrolactone (GBL), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), tetramethylurea (TMU), tetrahydrofuran (THF), m-cresol and ethyl acetate.

[0024] Preferably, the polymerization reaction further comprises an auxiliary agent;

[0025] Preferably, the auxiliary agent comprises a composite anti-yellowing agent, a catalyst and polytetrafluoroethylene nanocellulose.

[0026] Preferably, the composite anti-yellowing agent comprises an antioxidant, an ultraviolet light absorber and hydrophobic fumed silica;

[0027] Preferably, the antioxidant is selected from at least one of hindered phenol antioxidants and natural antioxidants;

[0028] Further preferably, the antioxidant is selected from at least one of antioxidant 2010 and tocopherol; more preferably, the antioxidant is antioxidant 2010 and tocopherol.

[0029] Preferably, the molar ratio of the antioxidant 2010 to tocopherol is 6-10:1-2; more preferably, the molar ratio of the antioxidant 2010 to tocopherol is 8:1.

[0030] Preferably, the ultraviolet light absorber is 2,4-dihydroxybenzophenone.

[0031] Preferably, the mass ratio of the antioxidant, the ultraviolet light absorber and the hydrophobic fumed silica is 10-15:3-6:2-4; further preferably, the mass ratio of the antioxidant, the ultraviolet light absorber and the hydrophobic fumed silica is 12:5:2.

[0032] Preferably, the amount of the composite anti-yellowing agent added is 0.1-8% of the total molar amount of diamine and dianhydride; further preferably, the amount of the composite anti-yellowing agent added is 0.1-5% of the total molar amount of diamine and dianhydride. More preferably, the amount of the composite anti-yellowing agent added is 2% of the total molar amount of diamine and dianhydride.

[0033] Preferably, the preparation method of the composite anti-yellowing agent is as follows: the preparation method of the composite anti-yellowing agent is as follows: take the antioxidant and add 10-15wt% ethanol to dissolve it, then add the ultraviolet light absorber and hydrophobic fumed silica, ultrasonicate for 10-30 minutes, and dry it.

[0034] Preferably, the catalyst is selected from at least one of diacetoacetate platinum, triethyl[(trimethoxysilyl)methylcyclopentadienyl)]platinum(IV) and stannous octoate;

[0035] Further preferably, the catalyst is platinum diacetoacetate, triethyl[(trimethoxysilyl)methylcyclopentadienyl)]platinum(IV) and stannous octoate.

[0036] Preferably, the molar ratio of the diacetylacetate platinum, triethyl [(trimethoxysilyl) methylcyclopentadienyl)] platinum (IV) and stannous octoate is 8-12:0.1-1:0.1-1; further preferably, the molar ratio of the diacetylacetate platinum, triethyl [(trimethoxysilyl) methylcyclopentadienyl)] platinum (IV) and stannous octoate is 10:0.1:0.5.

[0037] Preferably, the added amount of the catalyst is 0.5-1% of the total molar amount of the diamine and the dianhydride; more preferably, the added amount of the catalyst is 1% of the total molar amount of the diamine and the dianhydride.

[0038] Preferably, the molar ratio of the polytetrafluoroethylene nanocellulose to the total molar amount of diamine and dianhydride is 0.01-0.05:1; further preferably, the molar ratio of the polytetrafluoroethylene nanocellulose to the total molar amount of diamine and dianhydride is 0.02:1.

[0039] On the other hand, the present invention provides a method for preparing the above-mentioned flexible transparent polyimide film, comprising the following steps:

[0040] S1: mixing diamine and dianhydride with a solvent, and adding polytetrafluoroethylene nanocellulose to obtain a mixed solution;

[0041] S2: Add the composite anti-yellowing agent to the mixed solution, stir for 10-30 minutes, and then add the catalyst to obtain a precursor solution;

[0042] S3: pouring the precursor solution onto the substrate, drying for 10-40 min, removing part of the solvent, and obtaining a semi-dried film;

[0043] S4: placing the semi-dried film in an inert gas oven and subjecting it to high-temperature imidization to obtain the film.

[0044] Preferably, in S3, the drying temperature is 60-160°C;

[0045] Preferably, in S4, the temperature of the high temperature imidization is 200-280° C., and the time is 10-40 min.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] 1. The present invention prepares a polyimide film by mixing a specific plurality of dianhydrides and a specific plurality of diamines in a specific ratio, thereby significantly improving the optical properties of the polyimide film while obtaining better heat resistance and mechanical properties.

[0048] 2. The composite anti-yellowing agent prepared by the present invention through antioxidant 2010, tocopherol, 2,4-dihydroxybenzophenone, and hydrophobic fumed silica is combined with the diamine and dianhydride of the present invention to achieve the effect of significantly improving the optical properties of the polyimide film and reducing the yellowing index.

[0049] 3. The present invention achieves the effect of significantly improving the optical properties of the polyimide film while obtaining better heat resistance and mechanical properties by combining a specific catalyst, polytetrafluoroethylene nanocellulose with the diamine and dianhydride of the present invention.

[0050] 4. In summary, the present invention provides a flexible transparent polyimide film, which achieves the effect of significantly improving the optical properties of the polyimide film while obtaining better heat resistance and mechanical properties through specific components and ratios and optimized preparation methods. DETAILED DESCRIPTION

[0051] In order to make the technical means, creative features, purpose and effect of the present invention easy to understand, the present invention is further explained below in conjunction with specific embodiments, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without making creative work all belong to the protection scope of the present invention. It is worth noting that the raw materials used in the present invention are all common commercial products, and their sources are not specifically limited. The technology and scientific terms used in the embodiments have the meanings commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0052] Examples 1-6

[0053] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0054] Raw material composition:

[0055] 1. Its diamine and dianhydride and molar ratio are shown in Table 1:

[0056] Table 1. Diamines and dianhydrides of Examples 1-6

[0057] 2.

[0059] Solvent (DMSO);

[0060] Composite anti-yellowing agent (0.041 mol): antioxidant 2010 (0.0231 mol) and tocopherol (0.0029 mol), 2,4-dihydroxybenzophenone (0.011 mol), hydrophobic fumed silica (0.004 mol);

[0061] Catalyst (0.0205 mol): platinum diacetoacetate (0.01940 mol), triethyl[(trimethoxysilyl)methylcyclopentadienyl)]platinum(IV) (0.00019 mol) and stannous octoate (0.00096 mol);

[0062] Polytetrafluoroethylene nanocellulose (0.041 mol).

[0063] The preparation method of the composite anti-yellowing agent is as follows: taking antioxidant 2010 and tocopherol, adding 10-15% ethanol to dissolve, then adding 2,4-dihydroxybenzophenone and hydrophobic fumed silica, ultrasonicating for 10-30 minutes, and drying.

[0064] The preparation method comprises the following steps:

[0065] S1: mixing diamine and dianhydride with a solvent, and adding polytetrafluoroethylene nanocellulose to obtain a mixed solution;

[0066] S2: Add the composite anti-yellowing agent to the mixed solution, stir for 20 minutes, and then add the catalyst to obtain a precursor solution;

[0067] S3: pouring the precursor solution onto the substrate and drying it at 120°C for 35 min to remove part of the solvent and obtain a semi-dried film;

[0068] S4: Place the semi-dried film in an inert gas oven at 260°C for 30 minutes to obtain the film.

[0069] Comparative Examples 1-11

[0070] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0071] Compared with Example 1, the only difference is that the diamine and dianhydride in the raw material composition are different, as shown in Table 2:

[0072] Table 2. Diamines and dianhydrides of Comparative Examples 1-10

[0073]

[0074]

[0075] The rest is the same as Example 1.

[0076] Comparative Example 12

[0077] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0078] Compared with Example 1, the only difference is that the composite anti-yellowing agent in the raw material is different:

[0079] Specifically:

[0080] Composite anti-yellowing agent (0.041 mol): antioxidant 2010 (0.0257 mol) and tocopherol (0.0032 mol), 2,4-dihydroxybenzophenone (0.0121 mol);

[0081] The preparation method of the composite anti-yellowing agent is as follows: taking antioxidant 2010 and tocopherol, adding 10-15% ethanol to dissolve, then adding 2,4-dihydroxybenzophenone for 10-30 minutes, and drying.

[0082] The rest is the same as Example 1.

[0083] Comparative Example 13

[0084] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0085] Compared with Example 1, the only difference is that the composite anti-yellowing agent in the raw material is different:

[0086] Specifically:

[0087] Composite anti-yellowing agent (0.041 mol): antioxidant 2010 (0.0312 mol) and tocopherol (0.0039 mol), hydrophobic fumed silica (0.0059 mol);

[0088] The preparation method of the composite anti-yellowing agent is as follows: taking antioxidant 2010 and tocopherol, adding 10-15% ethanol to dissolve, then adding hydrophobic fumed silica, ultrasonicating for 10-30 minutes, and drying.

[0089] The rest is the same as Example 1.

[0090] Comparative Example 14

[0091] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0092] Compared with Example 1, the only difference is that the composite anti-yellowing agent in the raw material is different:

[0093] Specifically:

[0094] Composite anti-yellowing agent (0.041 mol): antioxidant 2010 (0.013 mol) and tocopherol (0.013 mol), 2,4-dihydroxybenzophenone (0.011 mol), hydrophobic fumed silica (0.004 mol);

[0095] The preparation method of the composite anti-yellowing agent is as follows: taking antioxidant 2010 and tocopherol, adding 10-15% ethanol to dissolve, then adding 2,4-dihydroxybenzophenone and hydrophobic fumed silica, ultrasonicating for 10-30 minutes, and drying.

[0096] The rest is the same as Example 1.

[0097] Comparative Example 15

[0098] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0099] Compared with Example 1, the only difference is the catalyst in the raw material:

[0100] Specifically:

[0101] Catalyst (0.0205 mol): platinum diacetoacetate;

[0102] The rest is the same as Example 1.

[0103] Comparative Example 16

[0104] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0105] Compared with Example 1, the only difference is the catalyst in the raw material:

[0106] Specifically:

[0107] Catalyst (0.0205 mol): triethyl[(trimethoxysilyl)methylcyclopentadienyl)]platinum(IV);

[0108] The rest is the same as Example 1.

[0109] Comparative Example 17

[0110] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0111] Compared with Example 1, the only difference is the catalyst in the raw material:

[0112] Specifically:

[0113] Catalyst (0.0205 mol): stannous octoate;

[0114] The rest is the same as Example 1.

[0115] Comparative Example 18

[0116] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0117] Compared with Example 1, the only difference is that the ratio of raw materials is different:

[0118] Diamine: BAPX 0.3mol, DMBZ 0.7mol;

[0119] Dianhydride: DSDA 0.76 mol, PDA 0.29 mol;

[0120] Composite anti-yellowing agent (0.205 mol): antioxidant 2010 (0.1155 mol) and tocopherol (0.0145 mol), 2,4-dihydroxybenzophenone (0.055 mol), hydrophobic fumed silica (0.02 mol);

[0121] Catalyst (0.0410 mol): platinum diacetoacetate (0.03880 mol), triethyl[(trimethoxysilyl)methylcyclopentadienyl)]platinum(IV) (0.00038 mol) and stannous octoate (0.00192 mol);

[0122] Polytetrafluoroethylene nanocellulose (0.205 mol).

[0123] The rest is the same as Example 1.

[0124] Comparative Example 19

[0125] A flexible and transparent polyimide film is prepared by polymerization of diamine and dianhydride:

[0126] Compared with Example 1, the only difference is that polytetrafluoroethylene nanocellulose is not added to the raw materials.

[0127] The rest is the same as Example 1.

[0128] Test Case

[0129] The film performance test method is as follows:

[0130] (1) The transmittance (Tr 550nm), yellowness index, and haze of polyimide film were tested using an X-rite Ci7800 spectrophotometer;

[0131] (2) The tensile strength, elongation at break, and elastic modulus of the polyimide film were tested using Shimadzu AG-X plus, 1 KN, test speed 5 mm / min, sample size 10 mm wide * 15 mm long, test gauge length: 50 mm, extensometer gauge length 20 mm.

[0132] (3) Glass transition temperature (Tg) was measured using a dynamic mechanical analyzer (DMA850) under the following test conditions:

[0133] The measurement was carried out in a nitrogen atmosphere at a load of 0.05 N and a heating rate of 3° C. / min in the temperature range of 200-400° C., and the inflection point of the curve with the maximum value was recorded as the glass transition temperature.

[0134] (4) Coefficient of thermal expansion (CTE) The test conditions using a thermomechanical analyzer (TMA 7100C) were as follows: load of 20 mN, heating rate of 5 °C / min, and temperature range of 50-200 °C.

[0135] The results are shown in Table 3.

[0136] Table 3. Film performance test results

[0137]

[0138]

[0139] From the data in Table 3, it can be seen that the light transmittance of the polyimide film prepared in Examples 1-6 of the present invention is greater than 89%, the yellowing index is less than 1.7, and the Tg is above 300°C. It has good optical transmittance, heat resistance, and good mechanical properties. Compared with Example 1, Comparative Examples 1-11 mainly changed the diamine and dianhydride, resulting in a significant decrease in its optical properties, and a decrease in heat resistance and mechanical properties; Comparative Examples 12-14 mainly changed the anti-yellowing agent, and it can be seen that its optical properties are significantly decreased, especially the yellowing index; Comparative Examples 15-19 changed the catalyst, raw materials and ratio, resulting in a significant decrease in its optical properties, and a decrease in heat resistance and mechanical properties. The specific raw materials and ratios of the present invention achieve a significant improvement in the optical properties of the imide film and ensure that it has good heat resistance and mechanical properties.

[0140] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A flexible and transparent polyimide film, characterized in that: The polyimide film is prepared by polymerization of diamine and dianhydride; The diamine comprises a first diamine and a second diamine; The first diamine is an aromatic diamine containing a rigid group; The second diamine is a diamine containing imidazole; The dianhydride comprises a first dianhydride and a second dianhydride; The first dianhydride is selected from at least one of 3,3,4,4-diphenylsulfone tetracarboxylic dianhydride, 4,4'-biphenyltetracarboxylic dianhydride and benzophenone tetracarboxylic dianhydride; The second dianhydride is selected from 2,2'-(1,4-piperazine dicarboxylic acid)-disuccinic anhydride or 2R,5R,7S,10S-naphthalenetetracarboxylic dianhydride.

2. The polyimide film according to claim 1, characterized in that: The first diamine is selected from at least one of 9,9-bis[4-(4-aminophenoxy)phenyl]xanthene, 2-(3,5-diaminophenyl)-9,9'-spirobifluorene, 2-(2,4-diaminophenyl)-9,9'-spirobifluorene and 2-bis(4-aminophenyl)hexafluoropropane.

3. The polyimide film according to claim 2, characterized in that: The second diamine is selected from at least one of 2-(4-aminophenyl)-5-aminobenzimidazole, 2-(3-aminophenyl)-5-aminobenzimidazole, diaminodiphenyl ether and 2,2'-dimethyl-4,4'-diaminobiphenyl.

4. The polyimide film according to claim 1, characterized in that: The molar ratio of the total amount of diamine to the total amount of dianhydride is 1-1.2:1-1.

2.

5. The polyimide film according to claim 1, characterized in that: The molar ratio of the first diamine to the second diamine is 3-7:2-6.

6. The polyimide film according to claim 1, characterized in that: The molar ratio of the first dianhydride to the second dianhydride is 6-9:1-4.

7. The polyimide film according to claim 1, characterized in that: The polymerization reaction is carried out in the presence of a solvent; the solvent is selected from at least one of N-methyl-2-pyrrolidone, dimethylacetamide, r-butyrolactone, dimethyl sulfoxide, dimethylformamide, tetramethylurea, tetrahydrofuran, m-cresol and ethyl acetate.

8. The polyimide film according to claim 1, characterized in that: The polymerization reaction further comprises an auxiliary agent; the auxiliary agent comprises a composite anti-yellowing agent, a catalyst and polytetrafluoroethylene nanocellulose.

9. The polyimide film according to claim 8, characterized in that: The added amount of the composite anti-yellowing agent is 0.1-8% of the total molar amount of diamine and dianhydride.

10. The polyimide film according to claim 8, characterized in that: The added amount of the catalyst is 0.5-1% of the total molar amount of the diamine and the dianhydride.

11. The polyimide film according to claim 8, characterized in that: The molar ratio of the polytetrafluoroethylene nanocellulose to the total molar amount of diamine and dianhydride is 0.01-0.05:

1.

12. The polyimide film according to claim 8, characterized in that: The composite anti-yellowing agent comprises an antioxidant, an ultraviolet light absorber and hydrophobic fumed silica.

13. The polyimide film according to claim 12, characterized in that: The antioxidant is selected from at least one of hindered phenol antioxidants and natural antioxidants.

14. The polyimide film according to claim 13, characterized in that: The antioxidant is selected from at least one of antioxidant 2010 and tocopherol.

15. The polyimide film according to claim 12, characterized in that: The ultraviolet light absorber is 2,4-dihydroxybenzophenone.

16. The polyimide film according to claim 12, characterized in that: The mass ratio of the antioxidant, the ultraviolet light absorber and the hydrophobic fumed silica is 10-15:3-6:2-4.

17. The polyimide film according to claim 12, characterized in that: The preparation method of the composite anti-yellowing agent is as follows: adding 10-15wt% ethanol to the antioxidant to dissolve it, then adding the ultraviolet light absorber and hydrophobic gas phase silica, ultrasonicating for 10-30 minutes, and drying.

18. The polyimide film according to claim 8, characterized in that: The catalyst is selected from at least one of diacetoacetate platinum, triethyl [(trimethoxysilyl) methylcyclopentadienyl)] platinum (IV) and stannous octoate.

19. The polyimide film according to claim 18, characterized in that: The catalyst is platinum diacetate, triethyl [(trimethoxysilyl) methylcyclopentadienyl)] platinum (IV) and stannous octoate; the molar ratio of platinum diacetate, triethyl [(trimethoxysilyl) methylcyclopentadienyl)] platinum (IV) and stannous octoate is 8-12: 0.1-1:0.1-1。 20. The method for preparing a flexible transparent polyimide film according to any one of claims 1 to 19, characterized in that: The following steps are involved: S1: mixing diamine and dianhydride with a solvent, and adding polytetrafluoroethylene nanocellulose to obtain a mixed solution; S2: Add the composite anti-yellowing agent to the mixed solution, stir for 10-30 minutes, and then add the catalyst to obtain a precursor solution; S3: pouring the precursor solution onto the substrate, drying for 10-40 min, removing part of the solvent, and obtaining a semi-dried film; S4: placing the semi-dried film in an inert gas oven and subjecting it to high-temperature imidization to obtain the film.

Citation Information

Patent Citations

  • A fully aromatic colorless transparent polyimide film and its preparation method

    CN108822296B

  • A transparent polyimide film and its preparation method

    CN109134858B

  • Semi-aromatic polyimide, preparation method and application thereof, and gas separation membrane containing the semi-aromatic polyimide

    CN110606951A

  • Low-yellowing colorless transparent polyimide film and preparation method thereof

    CN111073008A

  • High-temperature-resistant transparent polyimide film as well as preparation method and application thereof

    CN114479074A

Cited By

  • Low-yellowing fluorine-free semi-alicyclic polyimide composition and preparation method thereof

    CN120795318A

  • A low-yellowing fluorine-free semi-crystalline polyimide composition and a method for preparing the same

    CN120795318B